A Critical Study On William Shakespeare’s Soliloquies In Hamlet: Logotherapic Perspective - Shiny George; Dr.Nabamita Das (Revista Electronica de Veterinaria, 2024)
A critical analysis of William Shakespeare’s soliloquies in Hamlet is presented in this article. The study uses Viktor Frankl’s logotherapy, which is a theoretical combination of the three most significant tenets or pillars that form the basis of logotherapy. There are three fundamental assumptions of logotherapy, according to Frankl. Viktor Frankl’s theory is used to analyze Hamlet’s first soliloquy, emphasizing on "existential frustration" and its positive impact. Frankl asserts that there are three different meanings associated with the term "existential." The first one is to existence itself, which is the human way of being. Finding tangible significance in one’s own life, or will to meaning, is the third meaning, while the second meaning relates to the meaning of existence (Frankl 106). Thus, from the perspective of logotherapy, Hamlet’s soliloquies acquire a new significance. Furthermore, a fresh perspective on the analysis of William Shakespeare’s soliloquies in Hamlet is a cherry on top of Shakespeare’s brainchild, which is universal across all languages and civilizations and is born anew in every generation